Third-best carbon taxation: trading off emission cuts, equity, and efficiency - van der Ploeg, F; Rezai, A; Tovar, M (University of Oxford, 2024)
We analyse carbon taxes, lump-sum climate dividends, and changes to the level and progressivity of the income tax system that optimally trade off carbon emissions, equity, and efficient raising of public revenue while preserving budgetary neutrality and not using individualized lump-sum transfers. Such “third-best” policies include a carbon tax that exceeds the Pigouvian level and recycling of all carbon tax revenue via climate dividends for high (and our preferred) degrees of inequality aversion, even if this implies higher income taxes to meet existing revenue requirements. The carbon tax, climate dividends, and the progressivity of the income tax rise with the degree of inequality aversion. Our results are derived from a micro simulation model estimated from German data, which includes heterogenous households, an Exact Affine Stone Index demand system, and endogenous labour supply. We decompose the welfare effects of policy into emissions, equity, and efficiency components for different degrees of inequality aversion and climate damages.